2009
DOI: 10.1055/s-0029-1211249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Thyroxine and Carbimazole on Blood Levels of Biogenic Amines in Rat

Abstract: Circulating levels of 5-hydroxytryptamine (5HT), histamine, monoamine oxidase (MAO), histaminase, tri-iodothyronine (T3) and thyroxine (T4) were studied in L-thyroxine and carbimazole treated rats. Increased concentrations of 5-HT, histamine, glutamate, T3 and T4 were recorded in L-thyroxine-treated rats while plasma gamma-aminobutyric acid (GABA), MAO and histaminase levels were significantly decreased. Considerable reduction in 5-HT, glutamate, T3 and T4 with trend towards the rise in plasma levels of MAO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The histamine (H 2 ) receptor antagonist cimetidine and ranitidine reduce plasma T 3 -concentration [26] and another H 2 receptor antagonist, SK&F 93479 infl uences the circulating T 4 level [27]. In addition, experiments suggest that there is a signifi cant correlation between the biogenic amines and thyroid hormone values [28]. In the light of these observations, the infl uence of histamine defi ciency in our experiments on the non-biogenic hormone levels is not surprising.…”
Section: Resultsmentioning
confidence: 48%
“…The histamine (H 2 ) receptor antagonist cimetidine and ranitidine reduce plasma T 3 -concentration [26] and another H 2 receptor antagonist, SK&F 93479 infl uences the circulating T 4 level [27]. In addition, experiments suggest that there is a signifi cant correlation between the biogenic amines and thyroid hormone values [28]. In the light of these observations, the infl uence of histamine defi ciency in our experiments on the non-biogenic hormone levels is not surprising.…”
Section: Resultsmentioning
confidence: 48%
“…These results are consistent with the data of the current study. The possibility exists that the increase in plasma 5‐HT level may be due to its increased synthesis or decreased degradation, or both (Upadhyaya et al, 1993). For further support Cleare et al (1995) found that treatment of thyrotoxicosis reduces plasma 5‐HT level with a strong positive correlation between 5‐HT and T 3 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral nervous system has also been found to be dependent on the thyroid status. Alterations in the plasma monoamines have been studied in several animal models of thyrotoxicosis (Upadhyaya et al, 1993; Cleare et al, 1995). Catecholaminergic and serotononergic activities in the sympathetic nervous system are also dependent on the thyroid state (Zwaveling et al, 1996; Mano et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Upadhyaya et al (1993) demonstrated that in L-thyroxine-treated rats, histamine levels were found increased in the hypothalamus, thalamus and cortex of the rats, and that there was a positive correlation between circulating T3 and T4 levels and histamine. Csaba and Pállinger (2009a) demonstrated that very low histamine concentrations, not active on pain and inflammation, increased T3 mast cell content.…”
Section: Histamine and The Thyroidmentioning
confidence: 99%